STOCK SPLIT, FINANCIAL PERFORMANCE, SIZE, DAN LIKUIDITAS SAHAM DI BURSA EFEK INDONESIA - Nr, Erinos; Yurniwati, Yurniwati (Universitas Muhammadiyah Magelang, 2008)
The objective of the research to investigate stock split, financial performance, and size of firm were influence to liquidity of stock. Type of this research were verification descriptive, samples of this research are fro firm thai listing at BEI and used purposive sampling, sample representative is the firm taht doingstock split period 2002-2004 and firms aren?t do othercpolicy and announcement as time as with stock split. From that Cateria, only 25 firms used to analysis. There is one of firm has stock split 2 as long as observation period. To analysis data we used multiple regression method. The result of this research were stock aplit information does not influence for investor preference. That is dissapointed of no different taht significant abnormal return and liquidity of stock before and after stock split. The zise of firm size was influence to liquidity of stock but it was no significant. The financial performance of firm two from three financial ratio has influence and significant to liquidity of stock.